Susceptibilidade a movimentos de vertente e cheias repentinas no apoio à Protecção Civil - Pereira, Susana da Silva (2008)
Natural hazards assessment concerning Civil Protection is crucial for emergency situations prevention and mitigation. Among the natural hazards affecting the district of Oporto the landslides and the ?ash ?oods are over the last years those which presented hazard, mainly resulting from the increase of the human action on territory. Using Arcgis 9.1’s tools we’ve developed a Geodatabase joining cartographic information and related attributes concerning 3 main themes: historic information from ?oods ( 2002-2004) and landslides occurrences (1996-2006); conditioning factors (geomorphologic, hydrologic and lithologic ) as well as triggering factors (human or hidrogeomorphologic). Several conditioning factors were normalized and weighed in 3D Analyst e Spatial Analyst extensions in order to assess landslides and ?ash ?oods hazard at 1:50 000 scale. In landslide susceptibility assessment were considered factors such as lithology, morphology as geomorphologic dynamics. Concerning ?ash ?oods were pondered extreme precipitations, slope, lithology and morphological elements. Greater landslide susceptibility is registered in mountainous and intermediate relief areas in the eastern part of the district (along Douro’s Valley), at Valongo’s quartzite crests and at metamorphic hillslopes. Referring to ?ash ?oods larger susceptibility is located in mountainous areas where natural factors prevail. At the urban areas the human intervention plays a major role. It will be crucial to extend the occurrences database comprising a larger temporal range, producing natural hazard’s susceptibility cartography at a detailed scale, mainly in urban areas. This will contributes to build a District and Municipal base to Civil Protection work?ow and give the support instruments for land management at several intervention scales.